Effectiveness of the Islamic Education Management Study Program Using Alumni Tracer Study Data - Salabi, Agus Salim; Prasetyo, Muhammad Anggung Manumanoso; Halil, Hermanto; Maulina, Meta (Jurnal Akuntabilitas Manajemen Pendidikan, 2024)
This research aims to analyze the effectiveness of the Islamic Education Management Study Program (IEMSP) by implementing a tracer study involving its alums. The tracer study, a survey technique employed by higher education institutions, significantly enhances educational quality and program development. The research methodology is a mixed-method sequential exploratory approach with a concurrent embedded design, integrating qualitative and quantitative data. The primary focus is on qualitative data, complemented by quantitative data, gathered through interviews, participative observations, documentation studies, and the distribution of questionnaires to IEMSP alumni. The findings indicate that most IEMSP alumni successfully enter the workforce, demonstrating the effectiveness of the program's job placement efforts. The time required to secure the first job is generally short, with job roles predominantly in administrative and educational fields. These findings provide a solid basis for recommending curriculum updates, enhancements to career services, and strengthening partnerships with industries. The conclusion drawn from this research is that the program positively impacts the preparation of graduates for the workforce. The tracer study provides essential information for adjusting the curriculum to meet industry needs, introducing responsive teaching methods, and developing additional programs to enhance graduates' skills. The relevance of the tracer study results reflects the commitment of the Islamic Education Management Program to remain aligned with current developments, ensuring that graduates possess relevant knowledge and skills. Strategies such as field experience programs, industry partnerships, mentoring, and additional skills development are employed to improve alum absorption into the workforce. Continuous evaluation and improvement are undertaken to ensure the effectiveness of these strategies.